O estudo do Índice de Massa Corporal (IMC) por meio da experimentação e de aplicativo (APP) nas escolas da Região Metropolitana de Belém - PA - PUREZA, Eva Maria Joana Cruz da (2020)
In this work, a practical activity of the Body Mass Index (BMI) is carried out, using the equations of Quételet, Melão Jr. and Trefethen as an object of knowledge of the thematic unit “Life and Evolution” of the NCCB (National Common Curricular Base) for students in schools in the metropolitan region of Belém and in other environments (UFPA and squares). Initially, 10 volunteer students participated in this activity, 5 of whom were female (F) and 5 were male (M), with an average age of 17 years and 16 years; weight 55.055.15 kg and 67.3519.95 kg; 1.590.09 m and 1.650.15 m, respectively. In the end, they learn to use the anthropometric method and as 3 equations of the BMI, the media that were used for F and M. Thus, it is possible to make a preliminary monitoring of the students' health from the measurement of mass, weight and weight. BMI. Subsequently, we increased a sample in another school, UFPA and square and obtained satisfactory results for these measures. Finally, we tested the Biophysics - BMI application to perform these calculations and obtain the fastest values for BMI measurements that were used by hand or via calculator.